Evaluation of 334 paediatric chronic non-bacterial osteomyelitis cases: A multicentre cohort study defining clusters - Basaran, Ozge; Bayindir, Yagmur; Demir, Selcan; Yildiz, Adalet Elcin; Aliyev, Emil; Ulu, Kadir; Ozen, Seza (Oxford Univ Press, 2026)
Objectives This multicentre cohort study aimed to describe the clinical and demographic features of paediatric patients diagnosed with chronic non-bacterial osteomyelitis in Turkey and to identify patient clusters based on bone involvement.Methods A total of 334 paediatric chronic non-bacterial osteomyelitis patients from 21 paediatric rheumatology centres were included. Data on clinical presentation, imaging, and biopsy results were collected. A two-step cluster analysis was performed to classify patients by bone-site involvement, resulting in four distinct clusters.Results Axial-thoracic cluster, involving the vertebra, clavicle, and sternum, was more common in female patients and showed higher rates of skin involvement. Lower-extremity cluster, characterized by lower extremity bone involvement, included the largest number of patients. Unlike previous reports, the Turkish cohort had a higher proportion of male patients and a lower frequency of skin involvement. At a median follow-up of 42.4 months, 77.3% of patients achieved remission, while 22% experienced a relapse. Mandibular involvement, additional rheumatologic diseases, and localized bone pain were associated with an increased relapse risk.Conclusions This study highlights the clinical profile of paediatric chronic non-bacterial osteomyelitis in Turkey, marked by male predominance and low skin involvement. The identified bone-site clusters may help guide prognosis and should be validated in other populations.
Keywords: Chronic recurrent osteomyelitis; chronic non-bacterial osteomyelitis; paediatric; autoinflammatory bone disease; cluster